The activities of the prosecutor's office to suppress mass riots of a terrorist orientation, on the example of Kazakhstan and Kyrgyzstan - Zhambyl Smatov; Zhomart Nauatov; Taalaybek Ismanov (Universidad y Sociedad, 2024)
The article is devoted to the activities of the prosecutor's offices and law enforcement agencies in preventing mass disorders of a terrorist nature, based on materials from the Kyrgyz Republic and the Republic of Kazakhstan. The most acute and problematic issues of statistics related to crimes connected with terrorism are presented. Additionally, the article addresses problems in investigative practice and ways to solve crimes of a terrorist nature.